Periodization effects during short-term resistance training with equated exercise variables in females - Pelzer, T.; Ullrich, B.; Pfeiffer, M. (European Journal of Applied Physiology, 2017)
Purpose: During resistance training, volume and load can be altered either gradually (traditional periodization: TP) or with frequent changes between subsequent sessions (daily undulating periodization: DUP). We hypothesized that the periodization model employed would not impact upon training-induced adaptations when exercise variables are equated. Methods: Nineteen females (22.0 years, moderate resistance training experience of 27.9 months) performed 6 weeks of knee extensor training with 3 weekly sessions exercising one leg using TP and the contralateral leg using DUP. Training load varied between 40, 60, and 80% of one repetition maximum (1RM). Volume, range of motion, and time under tension were equated for each leg with a biofeedback software. Dynamometry, surface EMG and ultrasonography were used to determine temporal changes of knee extensor maximum voluntary strength (MVC), neural drive of the M. quadriceps femoris (QF) and vastus lateralis (VL) and rectus femoris (RF) muscle architecture. Results: Significant (P < 0.05) gains for isometric (TP 15%, DUP 13%) and isokinetic-concentric (TP 8%, DUP 10%) MVC and knee extensor 1RM (TP 18%, DUP 24%) occurred post training. VL and RF-muscle thickness showed significant (P < 0.05) increases ranging from 12 to 20% for TP and from 13 to 19% for DUP. Furthermore, significant (P < 0.05) increases in VL-pennation angle and VL-fascicle length occurred in both legs while QF EMG remained unchanged. No significant temporal differences were found between both models, displaying similar small to large effect sizes. Conclusion: Periodization is no adaptation trigger during short-term resistance training with equated exercise variables.